Answer:
Blank 1: (-7,0)
Blank 2: (-1,0)
Step-by-step explanation:
Plug x=0 into the equation and solve the resulting equation y=7 for y
Plug y=0 into the equation and solve the resulting equation 0=(x+1)(x+7) for x
1
How many cubes with side lengths of
3
cm does it take to fill the prism?
CON
cm
coln
cm
1 cm
Answer:
can you explain the question?
Step-by-step explanation:
in a unit circle, what is the relationship between arc length and central angle?
Answer:
The measure of an arc refers to the arc length divided by the radius if the circle. The arc measure equals the corresponding central angle measure, in radians.
Hue is arranging chairs. She can form 2 rows of a given length with 4 chairs left over, or 9 rows of that
same length if she gets 10 more chairs. Complete the equation and solve it to find how many chairs are in
that row length. In your equation, use the variable x to represent the number of chairs in each row.
The equation is
There are
chairs in each row.
Answer:
9x-10= 2x+4
x=2
Step-by-step explanation:
Jennifer has 4 pizzas that she cuts into eights. How many 1/8 size pieces does she have? please help mark you branlyest!!
Answer:
32
Step-by-step explanation:
4/1 / 1/8=32 :)
Keith has $500 in a savings account at the beginning of the summer. He wants to have at least $200 in the account by the end of the summer. He withdraws $35 each week for food, clothes and movie tickets. How many weeks can Keith withdraw money from his account?
Find the 75th term of the Arithmetic Sequence 15,11,7,3...
Answer:
-281
Step-by-step explanation:
Use the explicit formula
[tex]a_{n} = a_{1} + (n-1)d\\a_{n} = 15 + (n-1)(-4)\\a_{75} = 15 + (75-1)(-4)\\a_{75} = 15 - 300 + 4\\a_{75} = -281[/tex]
Mark ordered gummy bears and caramels for his candy shop. He ordered a total of twenty five pounds of there ingredients. Gummy bears cost $5 per pound, and caramels cost $8 per pound. He spent a total of $140.
A. Write a system of equations that describes the situation. Define each variable you use.
B. Solve the system of equations from part A using the substitution or elimination method. Write your solution using a complete sentence. Is the solution reasonable? Why or why not?
Answer:
20 pounds of Gummyballs and 5 pounds of caramel was ordered
Step-by-step explanation:
Let :
Gummyball = a
Caramel = b
a + b = 25 - - - (1)
5a + 8b = 140 - - - (2)
From (1)
a = 25 - b
Put into (2)
5(25 - b) + 8b = 140
125 - 5b + 8b = 140
125 + 3b = 140
3b = 15
b = 5
From a = 25 - b
a = 25 - 5
a = 20
Hence,
20 pounds of Gummyballs and 5 pounds of caramel was ordered
Solve for a
djəН
12
a =
✓ [?]
10
a
Pythagorean Theorem: a2 + b2 = c2
Enter
Answer:
a=[tex]\sqrt{44}[/tex]
Step-by-step explanation:
A^2+B^2=C^2
Substitute the values for what you know so:
a^2+10^2=12^2
Simplify:
a^2+100=144
-100 -100
------------------------
A^2=44
A=[tex]\sqrt{44}[/tex]
6 74/500 as a decimal (giving another chance for brainliest)
Answer:
6.148
Step-by-step explanation:
What is the value of 3x^4?
Answer:
243
Step-by-step explanation:
[tex]5( \sqrt{ {x}^{2} + 2x - 14} + x) = 20 \\ \\ \sqrt{ {x}^{2} + 2x - 14} + x= \frac{20}{5} \\ \\ \sqrt{ {x}^{2} + 2x - 14} + x= 4 \\ \\ \sqrt{ {x}^{2} + 2x - 14} = 4 - x\\ \\ {(\sqrt{ {x}^{2} + 2x - 14} )}^{2} = {(4 - x)}^{2} \\ \\ \cancel{ {x}^{2}} + 2x - 14 = 16 - 8x + \cancel{ {x}^{2} } \\ \\ 2x - 14 = 16 - 8x \\ \\ 2x + 8x = 16 + 14 \\ \\ 10x = 30 \\ \\ x = \frac{30}{10} \\ \\ x = 3 \\ \\ 3 {x}^{4} = 3 {(3)}^{4} = 3 \times 81 \\ \\ \huge \red {3 {x}^{4}= 243}[/tex]
what is the sum of 8bb-4bb
Answer:
4bb
Step-by-step explanation:
Answer:
4bb
Step-by-step explanation:
Because you need to combine like terms
Hope this helped!! :)
Stay safe and have a wonderful day/night!!!!!
Brainliest?!?!
(This is too easy)
NO ONE IS HELPINNGGGG PLZZZZ 30 PTS +brainliest
Answer:
360
Step-by-step explanation:
all quadrilateral angle sums are 360° no matter how you change it
A spherical balloon has a diameter of 4 feet. Approximate how many cubic feet of air this balloon holds. Use 3.14 as an approximation for pie, and give a numerical answer.
Answer:
3.764
Step-by-step explanation:
just try matgs is a tough de partoeProve one pair of opposite sides are congruent and parallel
Answer:
AB PARALLEL TO DC AND AD WITH BC
I need help with this
Answer:
3.5
Step-by-step explanation:
the median is the dotted lines.
median of girls height: 65.5
median of boys height: 69
69-65.5=3.5
9. A boy rides away from home in an automobile at the rate of 28 miles an hour and walks back at the rate of 4 miles an hour. The round trip requires 2 honrs. How far does he ride?
Answer:
9. A loebskesşbxksjlejs
Which answer choice correctly identifies the missing information in the problem? Joey and Kirk are in the 6th grade. Kirk is 5 feet 4 inches tall. Joey is 4 feet 8 inches tall. How much taller is Kirk than Joey?
Answer:Kirk is taller than Joey by 8 inches
Step-by-step explanation:
Step 1
Kirk's height is given as =5 feet 4 inches tall.
Joey's height 4 feet 8 inches tall
Difference in height = 5 feet 4 inches
- 4 feet 8 inches
=
Step 2
Bear in mind that 12 inches = 1 feet . Now,8 cannot be subtracted from 4 , so we borrow 1 feet from 5feet, which is equivalent to 12 inches and add to inches so it becomes
4 feet (12+4)inches = 4 feet 16inches
- 4 feet 8 inches - 4 feet 8 inches
= 8 inches
Therefore Kirk is taller than Joey by 8 inches
3. Use distributive property to simplify
a. (-6) * [(-12) + (25)]
C. (+6) * [(-17) + (+28)]
e. (+7) * [(-12) – (+6)]
Solve this answer with solution please
Answer:
see the answersStep-by-step explanation:
to understand thisyou need to know about:PEMDAStips and formulas:orders of PEMDAS:
parenthesesexponentmultiplication ordivisionaddition orsubstractionleft to rightlet's solve:a)
remove first parentheses and add: -6×[-12+26] =-6×[14]remove third parentheses and multiply:-6×14=-84c)
remove first parentheses and add:(6)×[-17+28]=6×[11]remove third parentheses and multiply: 6×11=66e)
remove first parentheses and substract:7×[-12-(6)]=7×[-12+(-6)]=7×[-18] multiply:7×[-18]=-126HELP ANSWER FAST!!!!
Somebody help me please
Answer:
The second one
Graph the function y = 4x4 – 8x2 + 4. Which lists all of the turning points of the graph?
(0, 4)
(–1, 0) and (1, 0)
(–1, 0), (0, 4), and (1, 0)
(–4, 0), (–1, 0), (0, 4), and (1, 0)
in case you are wondering, there is no graph.
Answer:
[tex]4(x + 1)^{2}(x - 1)^{2}[/tex]
Step-by-step explanation:
STEP 1:
The equation at the end of step 1
[tex]((4 (x^4)) - 2^3x^2) + 4[/tex]
STEP 2:
The equation at the end of step 2:
[tex](2^2x^4 - 2^3x^2) + 4[/tex]
STEP 3:
STEP 4: Pulling out like terms
4.1 Pull out like factors:
[tex]4x^4 - 8x^2 + 4 = 4(x^4 - 2x^2 + 1)[/tex]
Trying to factor by splitting the middle term
4.2 Factoring [tex]x^4 - 2x^2 + 1[/tex]
The first term is, [tex]x^4[/tex] its coefficient is 1.
The middle term is, [tex]-2x^2[/tex] its coefficient is -2.
The last term, "the constant", is +1.
Step-1: Multiply the coefficient of the first term by the constant 1 • 1 = 1
Step-2: Find two factors of 1 whose sum equals the coefficient of the middle term, which is -2.
-1 + -1 = -2 That's it
Step-3: Rewrite the polynomial splitting the middle term using the two factors found in step 2 above, -1 and -1
x4 - 1x2 - 1x2 - 1
Step-4 : Add up the first 2 terms, pulling out like factors :
x2 • (x2-1)
Add up the last 2 terms, pulling out common factors :
1 • (x2-1)
Step-5 : Add up the four terms of step 4 :
(x2-1) • (x2-1)
Which is the desired factorization
Trying to factor as a Difference of Squares:
4.3 Factoring: x2-1
Theory : A difference of two perfect squares, A2 - B2 can be factored into (A+B) • (A-B)
Proof : (A+B) • (A-B) =
A2 - AB + BA - B2 =
A2 - AB + AB - B2 =
A2 - B2
Note : AB = BA is the commutative property of multiplication.
Note : - AB + AB equals zero and is therefore eliminated from the expression.
Check : 1 is the square of 1
Check : x2 is the square of x1
Factorization is : (x + 1) • (x - 1)
Trying to factor as a Difference of Squares:
4.4 Factoring: x2 - 1
Check : 1 is the square of 1
Check : x2 is the square of x1
Factorization is : (x + 1) • (x - 1)
Multiplying Exponential Expressions:
4.5 Multiply (x + 1) by (x + 1)
The rule says : To multiply exponential expressions which have the same base, add up their exponents.
In our case, the common base is (x+1) and the exponents are :
1 , as (x+1) is the same number as (x+1)1
and 1 , as (x+1) is the same number as (x+1)1
The product is therefore, (x+1)(1+1) = (x+1)2
Multiplying Exponential Expressions:
4.6 Multiply (x-1) by (x-1)
The rule says : To multiply exponential expressions which have the same base, add up their exponents.
In our case, the common base is (x-1) and the exponents are :
1 , as (x-1) is the same number as (x-1)1
and 1 , as (x-1) is the same number as (x-1)1
The product is therefore, (x-1)(1+1) = (x-1)2
Final result :
4 • (x + 1)2 • (x - 1)2
I NEED HELP AGAIN 6.0
Answer:
(-3,2) (-2,4)
Step-by-step explanation:
Origin to (-3,2)
Other dot (-2,4)
A chef bought 0.56 kilograms of almonds and 0.4 kilograms of pecans. How many kilograms of nuts did the chef buy in all?
Answer:
0.96 kg
Step-by-step explanation:
0.56+0.40=0.96
95.4
Add the numbers of kilograms. Remember to line up the decimal points. You can write extra zeroes to make equivalent decimals.
The mid point of a given line segment must lie on the given line segment
true or false
Write the equation of the line in slope-intercept form given the graph below.
Answer:
y=-2/3x-1
Step-by-step explanation:
Answer:
y=-2/3x-1
Step-by-step explanation:
-4.368 - 3.86 And also 16.37 + (-29.786)
Answer:
-8.228 and -13.416
Step-by-step explanation:
math
86, 82, 78, 74 , what is the 40th sequence
Answer:
The numbers slowly decrease by 4 so we can determine that the 40th sequence is -70.
Step-by-step explanation:
A man shares a $1,200,00 inheritance between his 3 sons in ratio 1: 3: 6. Calculate the difference between the largest share and the smallest share
Answer:
60000
Step-by-step explanation:
You should treat the first son with the 1 ratio as x. Because of this, the second son would be 3x and the third would be 6x. All of them need to equal 120000 so 10x=120000. Next you isolate the and x= 12000. Fill in 1200 for x and the first son gets 12000, the second gets 36000, and the third gets 72000. Lastly you subtract and you get 60000.
Write your answer in scientific notation.
(5.1x10^7)+(1.3 x 10^6)
How do you simplify 14.938 - 14.93 ?
Please help
Answer:
0.008
Step-by-step explanation:
To know the steps pls look at the pic above